Physiological maturity of quaresmeira seeds - Lopes, José Carlos; Dias, Paulo César; Pereira, Márcio Dias (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to study the maturation process of Tibouchina granulosa Cogn. seeds. Each inflorescence was identified in the day of its respective anthesis. Samples of fruits and seeds were collected weekly, and diameter, weight, color, moisture content and dry matter were determined. After seed extraction, analyzes were made for coloring, moisture content, dry matter, 1,000 seeds mass, speed and percentage of germination. Experimental design was carried out in a completely randomized block with four replications. Analysis of data obtained led to the following conclusions: seeds physiological maturity occurred 84 to 105 days, and seed harvest should be done between 84 to 98 days after the anthesis. The parameters which best characterized seed physiological maturity and the time for harvesting were moisture content and dry matter weight. The largest germination percentage was verified in extracted seeds from 77 until 105 days after the anthesis, and seeds vigor increased until 91 days. The size and color of fruits and seeds demonstrated efficiency as maturation parameters. Fruits initial dehiscences occurred after 105 days of the anthesis. Tibouchina granulosa presented seed dormancy after maturation.